2021
DOI: 10.1080/15226514.2021.1876627
|View full text |Cite
|
Sign up to set email alerts
|

Constructed wetland for improved wastewater management and increased water use efficiency in resource scarce SAT villages: a case study from Kothapally village, in India

Abstract: Evaluation a field-scale of constructed wetland (CW) for the treatment of rural wastewater (WW), in resource-scarce semi-arid tropic (SAT) villages, to provide improved wastewater management and increased water use efficiency, was the main objective of this study. A CW was commissioned in Kothapally village of Telangana to treat the wastewater generated from 100 households. The CW was vegetated with Typha latifolia and Canna indica. Average COD, sulfate and inorganic nitrogen removal efficiencies observed were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…was typically not used for drinking or fishing and was only occasionally used for irrigation (Datta et al, 2021;Maiga et al, 2015). In the water, sediment, and adjoining soil samples, we quantified the DNA markers of the fecal indicator (Escherichia coli) to investigate the persistence of fecal bacteria; 16S rRNA gene copies to track the trends in the total bacterial count; and the anthropogenic antibiotic resistance gene markers-intI1, sul1, to investigate the overall trends in antibiotic resistance potential in WRPs.…”
Section: Core Ideasmentioning
confidence: 99%
See 1 more Smart Citation
“…was typically not used for drinking or fishing and was only occasionally used for irrigation (Datta et al, 2021;Maiga et al, 2015). In the water, sediment, and adjoining soil samples, we quantified the DNA markers of the fecal indicator (Escherichia coli) to investigate the persistence of fecal bacteria; 16S rRNA gene copies to track the trends in the total bacterial count; and the anthropogenic antibiotic resistance gene markers-intI1, sul1, to investigate the overall trends in antibiotic resistance potential in WRPs.…”
Section: Core Ideasmentioning
confidence: 99%
“…We sampled seven WRPs and contrasted them with two ponds (sites H and I) that did not directly receive domestic wastewater and were used for irrigation (P–I) and pisciculture (P–P), respectively. We observed that the water from the targeted WRPs was typically not used for drinking or fishing and was only occasionally used for irrigation (Datta et al., 2021; Maiga et al., 2015). In the water, sediment, and adjoining soil samples, we quantified the DNA markers of the fecal indicator ( Escherichia coli ) to investigate the persistence of fecal bacteria; 16S rRNA gene copies to track the trends in the total bacterial count; and the anthropogenic antibiotic resistance gene markers— int I1, sul 1, to investigate the overall trends in antibiotic resistance potential in WRPs.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has to be noted that from the 55 studies in the review, only 12 out rightly mentioned water reuse. As mentioned in the studies, the most reuse activity for the water from CWs is irrigation, with 12 mentions (Andreo-Martínez et al, 2017;Ayaz et al, 2015;Bekkari et al, 2022;Datta et al, 2021;Fountoulakis et al, 2017;Kilingo et al, 2022;Muduli et al, 2022;Nivala, Abdallat, et al, 2019;Oliveira et al, 2021;Paulo et al, 2013;Shingare et al, 2017;Song et al, 2021). The second most cited activity was landscaping, with three mentions (Bekkari et al, 2022;Kilingo et al, 2022;Oliveira et al, 2021); the reuse of purified effluent for urban green spaces and golf courses is widespread, as illustrated by (Bekkari et al, 2022) in the village of Temacine, Algeria.…”
Section: Emerging Themes In Domestic Wastewater Treatment By Cwsmentioning
confidence: 99%
“…Biomass use was one of the other interesting issues in the studies. The nutrient-rich plants used in CWs, according to the studies by (Datta et al, 2021;Oliveira et al, 2021), can be used as livestock fodder. This is clearly illustrated in the city of Kothapally, India, where 500 kgs of biomass were harvested after 45 days and were used to feed the livestock of the nearby farmers (Datta et al, 2021).…”
Section: Emerging Themes In Domestic Wastewater Treatment By Cwsmentioning
confidence: 99%
“…[20][21][22] Similarly, a lot of work at the lab and pilot scale has been done on different types of macrophytes and also to ascertain the role of microorganisms in CW for escalating the efficiency of treatment. 3,[23][24][25][26] Research related to the mode of operation like changes in the flow pattern, different methods of aeration, recirculation, and so on, 5,[27][28][29] and operational factors like change in depth, variation in hydraulic loading rate, and different hydraulic retention time has also proved to be of importance in improving the efficiency of the system, [30][31][32][33] and have been studied extensively.…”
mentioning
confidence: 99%